DISTINCT CULTURAL TRADITIONS IN JUGS SHAPING: RESEARCH EVIDENCE FROM ALBANIAN-SARMATIAN AND EARLY MEDIEVAL SITES OF DAGESTAN - Suhanov, Evgenij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2024)
The “History of Pottery” laboratory at the Institute of Archeology of the Russian Academy of Sciences has been conducting research on the persistence of various skills involved in shaping clay vessels. This research aims to identify the threshold within morphological diversity where random variations end and features reflecting the characteristics of past populations begin. This article presents new data on the stability of different vessel shape parameters, gathered from ethnographic and experimental studies. It focuses on jugs, the most common pottery type found in Albanian-Sarmatian and early medieval burial grounds of Dagestan. The article compares these sites and performs a quantitative analysis of their similarity based on various vessel shape parameters. The analysis revealed two distinct cultural traditions in jug shaping based on stable form parameters. The earlier tradition is represented by sites of the Albanian-Sarmatian located in the Caspian Dagestan, mainly in its lowland area and on the border of the lowland and foothill zones – in the Sirtich, Sharakun and Lvov burial grounds. The later tradition, common at sites of the 8th-10th centuries, is found on the border of the foothill and mountain zones – in the Agachkalinsky, Arkassky burial grounds. High similarity of shapes in early medieval Bezhta and Verkhnechiryurt burial grounds with materials from the later tradition confirms this distinction. Chronological and territorial differences between these material groups support the use of stable form parameters as a reliable marker for identifying distinct and unrelated pottery traditions in archaeological ceramics.
Keywords: jugs; vessel shapes; cultural traditions; skill persistence of potters; Dagestan